PROFESSIONAL ABILITY OF PROSPECTIVE ELEMENTARY SCHOOL TEACHER THROUGH PROJECT-BASED LEARNING MODEL IN PRIMARY EDUCATION - Sarah Fazilla; Yullita Molliq Rangkuti (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2023)
Today's rapid technological advances must be accompanied by the professional competence of educators, especially in integrating technology and project-based learning models. This research is a systematic review study to analyze the professional competency of teachers, the PjBL model in Primary Education, and the relationship between the professional abilities of teachers to implement the PjBL model in learning at elementary school. An article search through the Google Scholar database found 33600 journal articles after inclusion and exclusion were carried out. Ten journals were obtained for systematic review. From the results of a systematic study, it was found that there were journals that stated that the teacher's motivation in using the PjBL model had a direct impact on increasing the ability of children to develop their mindset towards the material being taught. It was also found that the ability to implement the PjBL model was combined with other learning models and approaches, and the ability of teachers to apply the technology-assisted PjBL model, so, in general, the competence of prospective elementary school teachers can be improved through the PjBL model. Based on the findings of a review of ten relevant journals, it can be said that using the PjBL model in learning presents some difficulties, particularly at the basic education level. Therefore, higher education institutions are expected to design the models and techniques to prepare student-teacher candidates to develop professional competence by innovating, being creative, and utilizing technology through project-based learning.